2023
DOI: 10.17507/jltr.1403.19
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students' Knowledge and Attitude Towards Medical Writing Skills in the English Language

Abstract: Medical Writing skills in the English language is challenging for those having English as their second language. Hence, this study focuses on understanding the knowledge and attitude toward medical writing skills in the English Language among undergraduate nursing students in Saudi Arabia. This study adopted an exploratory study design. It included all nursing students enrolled in the first year of the undergraduate nursing program in Abha (n=80) and Muhayil (n=80) female campuses of King Khalid University (KK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The relationship between educational institutions and healthcare systems is crucial, aimed at tackling the difficulties experienced by nursing students during their clinical education, especially while receiving hands-on training from nurses and medical personnel. A recent study by Banafi reported that nursing students of the researcher's University presented good knowledge and positive attitudes toward English medical writing skills [49] .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between educational institutions and healthcare systems is crucial, aimed at tackling the difficulties experienced by nursing students during their clinical education, especially while receiving hands-on training from nurses and medical personnel. A recent study by Banafi reported that nursing students of the researcher's University presented good knowledge and positive attitudes toward English medical writing skills [49] .…”
Section: Discussionmentioning
confidence: 99%